Environmental engineering : prevention and response to water-, food-, soil-, and air-borne disease and illness - Nemerow, Nelson L.; Agardy, Franklin J.; Sullivan, Patrick; Salvato, Joseph A. (Wiley / John Wiley & Sons, 2009)
First published in 1958, Salvato's Environmental Engineering has long been the definitive reference for generations of sanitation and environmental engineers. Approaching its fiftieth year of continual publication in a rapidly changing field, the Sixth Edition has been fully reworked and reorganized into three separate, succinct volumes to adapt to a more complex and scientifically demanding field with dozens of specializations.Updated and reviewed by leading experts in the field, this revised edition offers new coverage of appropriate technology for developing countries. Stressing the practicality and appropriateness of treatment, the Sixth Edition provides realistic solutions for the practicing public health official or environmental engineer.This volume, Environmental Engineering: Prevention and Response to Water-, Food-, Soil-, and Air-borne Disease and Illness , Sixth Edition, covers: Disease transmission by contaminated waterFood-borne diseasesControl of diseases of the air and land Appropriate technology for developing countries